(untitled) (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Aloe vera has been used traditionally for healing burn and inflammation. Though, the evidence for the effectiveness of aloe vera for healing burn is not sufficient. Objective: The aim of this study was to assess the effectiveness of aloe vera gel in management of superficial burn in children. Methods: This retrospective study was taken place in the Department of Burn and Reconstructive Surgery, Bangladesh Shishu Hospital & Institute, Dhaka and other two privet clinics at Dhaka, from September, 2019 to March, 2022. Total 47 patients with superficial partial thickness burn was included in the study. Results: In this study, majority (48.94%) patients were belonged to the age group of £24 months. The mean age was found 38.9±26.31 months. The current study observed that almost two third (61.70%) patients were male. In our study, majority (63.83%) patients stayed hospital for 1-5 days. In the present study, mean (±SD) pain relief time was 3.56±1.24 days and mean (±SD) wound healing time was found 8.19±1.6 days. The current study observed that only 3(6.38%) patients had found wound infection. In current study showed that mean treatment cost was found 76.46±31.88 Taka. Conclusion: Aloe vera gel facilitated early pain alleviation, wound healing, and costeffective superficial burn treatment in children. Therefore, it can be utilized to treat superficial burns in children to get better results. DS (Child) H J 2021; 38(1): 39-43